Pembelajaran PPKn di Perguruan Tinggi sebagai Alternatif Pendidikan Demokrasi dan Hak Asasi Manusia dalam Upaya Membangun Masyarakat Madani - Jauhan Budiwan, Erna Gesti F (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2019)
The purpose of writing this article is to analyze the importance of PPKN learning in universities. PPKN in higher education is a subject must be taught in accordance with UU No. 20 Th 2003 concerning the national education system. The essence of PPKN learning is about understanding democracy and human rights. Philosophically, the State's interest in learning democracy and human rights is to refer to civil society in Indonesia. The method used in this paper is a review of literature, namely analyzing a starategi to achieve a goal using literature theories. The results in this writing that the PPKN learning in higher education is very appropriate to make a nation's society a good citizen.